Peran Keluarga dalam Membentuk Pola Pembiasaan Pendidikan Agama Islam pada Anak Usia Dini - Wardana, Raja; Nana, Nana; Azka, Azka (Journal of Community Development and Empowerment, 2025)
The family plays a central role in shaping the pattern of Islamic religious education habituation in early childhood, as the family environment is the first place where a child receives education. Instilling religious values from an early age becomes a crucial foundation in building strong Islamic character. This study aims to examine the role of the family, especially parents, in implementing patterns of Islamic religious education habituation in early childhood. The research method used is descriptive qualitative with a literature study and empirical observation approach. The results show that the family acts as the primary role model through daily behavior, communication, and religious practices, such as encouraging children to pray, read the Qur'an, and learn supplications. This habituation pattern requires consistency and positive reinforcement so that religious values can be deeply instilled. In conclusion, the family's role is vital in shaping a child's religious personality, which will serve as their provision for facing future life challenges.